2011
DOI: 10.1186/1471-2105-12-s15-s1
|View full text |Cite
|
Sign up to set email alerts
|

Towards mainstreaming of biodiversity data publishing: recommendations of the GBIF Data Publishing Framework Task Group

Abstract: BackgroundData are the evidentiary basis for scientific hypotheses, analyses and publication, for policy formation and for decision-making. They are essential to the evaluation and testing of results by peer scientists both present and future. There is broad consensus in the scientific and conservation communities that data should be freely, openly available in a sustained, persistent and secure way, and thus standards for 'free' and 'open' access to data have become well developed in recent years. The questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…Progress would be promoted if data publishing was regarded as having the same status as traditional scientific (peer-reviewed) scholarly publishing (Chavan and Ingwersen 2009). In accord with this, we recommend an early uptake of recommendations of its Data Publishing Framework Task Group (GBIF 2009e;Moritz et al 2011) and incentivisation mechanisms proposed Chavan and Ingwesen 2009;Ingwersen and Chavan 2011;Goddard et al 2011).…”
Section: Promoting Ease-of-use and Incentives For Wide-usementioning
confidence: 99%
“…Progress would be promoted if data publishing was regarded as having the same status as traditional scientific (peer-reviewed) scholarly publishing (Chavan and Ingwersen 2009). In accord with this, we recommend an early uptake of recommendations of its Data Publishing Framework Task Group (GBIF 2009e;Moritz et al 2011) and incentivisation mechanisms proposed Chavan and Ingwesen 2009;Ingwersen and Chavan 2011;Goddard et al 2011).…”
Section: Promoting Ease-of-use and Incentives For Wide-usementioning
confidence: 99%
“…Data sharing can have practical challenges (Borgman, 2012) and researchers may be cautious (Huang et. al., 2012;Vogeli et al 2006;Walport and Brest, 2011), but there is a strong tradition of sharing resources in some fields (e.g., software in computer science), for some types of general data (e.g., surveys: UKDA, 2007) and for specialist information, such as species records in biodiversity research (Faith et al, 2013;Moritz et al, 2011;see also: Barve, 2014) and human biological samples (Chen, 2013). Moreover, there is an argument that all publically funded research should publish its data (Arzberger, et al 2004;Walport and Brest, 2011), and many funding agencies, including the European Commission (European Commission, 2015), the National Science Foundation (NSF) (Hswe and Holt, 2011) and the UK's Wellcome Trust (Wellcome, 2015), require scientific data sharing when possible for their funded projects.…”
Section: Introductionmentioning
confidence: 99%
“…Many successful cases that reused shared data to produce new research have been reported in the past, such as species records in biodiversity research (Faith et al, 2013;Moritz et al, 2011;Barve, 2014) and human biological samples (Chen, 2013). Researchers discovered three new species of the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 s l i b J o u r n a l o f I n f o r m a t i o n M a n a g e m e n t 4 bacterial endosymbiont Wolbachiapipientis in the three different species of fruit fly using the raw data deposited in Trace Archive (Salzberg, 2005).…”
Section: Background and Related Workmentioning
confidence: 99%